Xuebijing Injection Maintains GRP78 Expression to Prevent Candida albicans–Induced Epithelial Death in the Kidney - Shang, Ting; Yu, Qilin; Ren, Tongtong; Wang, Xin-Tong; Zhu, Hongyan; Gao, Jia-Ming; Pan, Guixiang; Gao, Xiumei; Zhu, Yan; Feng, Yuxin; Li, Ming-Chun (Frontiers in Pharmacology, 2020)
Sepsis and septic shock threaten the survival of millions of patients in the intensive care unit (ICU). Secondary fungal infections significantly increased the risk of mortality in sepsis patients. Chinese medicine Xuebijing injection (XBJ) has been routinely used as an add-on treatment to sepsis and septic shock in China. Our network pharmacology analysis predicted that XBJ also influences fungal infection, consisting with results of pioneer clinical studies. We conducted in vivo and in vitro experiments to verify this prediction. To our surprise, XBJ rescued mice from lethal Candida sepsis in a disseminated C. albicans infection model and abolished the colonization of C. albicans in kidneys. Although XBJ did not inhibit the growth and the virulence of C. albicans in vitro, it enhanced the viability of 293T cells upon C. albicans insults. Further RNA-seq analysis revealed that XBJ activated the endoplasmic reticulum (ER) stress pathway upon C. albicans infection. Western blot confirmed that XBJ maintained the expression of GRP78 in the presence of C. albicans. Interestingly, key active ingredients in XBJ (C0127) mirrored the effects of XBJ. C0127 not only rescued mice from lethal Candida sepsis and prevented the colonization of C. albicans in kidneys, but also sustained the survival of kidney epithelial cells partially by maintaining the expression of GRP78. These results suggested that XBJ may prevent fungal infection in sepsis patients. Pre-activation of ER stress pathway is a novel strategy to control C. albicans infection. Network pharmacology may accelerate drug development in the field of infectious diseases.